Teachers' Experiences in Teaching Arabic in Madrasah: A Multisite Study - Nufus, Hayatun; Husnan, Husnan; Nurjannah, Nurjannah; Nasarudin, Nasarudin (FKIP - Universitas Riau, 2025)
Based on a descriptive qualitative study, this research aims to explore teachers' experiences in teaching Arabic in three Islamic-based secondary schools (MTs and MAs) in Mataram. Arabic has an important role in Islamic education, thus understanding its teaching practices is very relevant. This study specifically addresses three main aspects of the learning process, namely planning, implementation and evaluation. Data were obtained through in-depth interviews and classroom observations of nine purposively selected teachers. The results show that teachers use various teaching methods such as two-way interaction, audiolingual, lecture, and qira'ah which are adjusted to the characteristics of students and school conditions. Teachers also actively participate in training and discuss with peers to improve professional competence. The main challenges faced include students' low basic Arabic reading skills, limited facilities, and lack of learning motivation. To overcome this, teachers apply differentiated learning strategies, vocabulary grouping and building positive emotional relationships with students. Evaluation is done formatively and summatively by utilizing technology. The results confirm that successful teaching of Arabic requires innovation, reflection and a deep understanding of students' needs.